Comparison of Four Different Shields for Birdcage-Type Coils with Experiments and Numerical Calculations - LIU, WANZHAN (2006)
Four 12-rung linear birdcage-type coils were built to experimentally examine the effects of the end-ring/shield configuration on radiofrequency magnetic field (B(1)) homogeneity and SNR at 125 MHz. The coil configurations include (a) a cylindrical shield (conventional), (b) a shield with annular extensions to closely shield the end-rings (surrounding shield), (c) a shield with annular extensions connected to the rungs (solid connection), and (d) a shield with radially oriented conductors connected to the rungs (radial connection). These coils were also modeled closely with finite difference time domain (FDTD) methods to corroborate experimental findings. Images of a human head were acquired, and the signal-to-noise ratio (SNR) was measured on the central axial, sagittal, and coronal slices. B(1) field homogeneity in the unloaded coils was assessed on images of an oil phantom. Among the four configurations, the solid connection configuration has a lower SNR than the conventional configuration and the surrounding shield configuration but a higher SNR than the radial connection. Although there is no significant difference between the overall SNR of the conventional configuration and the surrounding shield configuration, the surrounding shield configuration has the potential to be tuned to higher frequencies than the conventional configuration. The conventional birdcage coil results in the most homogeneous B(1) field in the oil phantom. Numerical results are also compared with the experimental results.